DETERMINATION OF ANTIOXIDANT CAPACITY AND GALLIC ACID CONTENT IN ETHANOLIC EXTRACT OF PUNICA GRANATUM L. LEAF - P, Sreedevi; K, Vijayalakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present research work was carried out to evaluate the antioxidant potential of ethanolic extract of Punica granatum leaf (EPGL) that belongs to the family of Punicaceae and determine its gallic acid (GA) content using chromatography method. Methods: Six complementary test systems, namely, 1,1-diphenyl 2-picryl hydrazine (DPPH), hydrogen peroxide (H2O2), superoxide (SO), nitric oxide (NO), hydroxyl (OH) radical scavenging, and reducing power activities were analyzed for determining antioxidant activity of EPGL. The simple and novel chromatography techniques such as thin-layer chromatography (TLC) and high-performance liquid chromatography (HPLC) were used for the detection and quantification of GA in EPGL. Results: IC50 values of EPGL were found to be 136 Î¼g/ml for DPPH, 88.5 Î¼g/ml for H2O2, 16.8 Î¼g/ml for SO, 96.5 Î¼g/ml for NO, and 143 Î¼g/ml for OH. The ascorbic acid (AA) and GA were used as standard compounds. The absorbance of EPGL in reducing power assay was found to be 0.18 at 100 Î¼g/ ml, while AA and GA absorbance was found to be 0.24 and 0.4 at the same concentration. The amount of GA in EPGL was found to be 1.189 mg/g. Conclusion: These findings suggested that EPGL could be a potential source of natural antioxidant, and HPLC method used for the determination of GA is simple, precise, accurate, and suitable for routine analysis of GA in EPGL.